2012
DOI: 10.1155/2012/684510
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and the Healing of Bone Fracture: The Current State of Evidence

Abstract: Background. The effect of vitamin E on health-related conditions has been extensively researched, with varied results. However, to date, there was no published review of the effect of vitamin E on bone fracture healing. Purpose. This paper systematically audited past studies of the effect of vitamin E on bone fracture healing. Methods. Related articles were identified from Medline, CINAHL, and Scopus databases. Screenings were performed based on the criteria that the study must be an original study that invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 41 publications
0
4
0
13
Order By: Relevance
“…Vitamin C supplementation accelerated fracture repair that included prominent chondrocyte hypertrophy at day 10 and a well‐developed fibrocartilaginous callus with osteoid formation on day 15, and faster transition of the cartilaginous callus into the bony callus . Unlike vitamin C, vitamin E supplements in the form of α‐tocopherol appear to be most beneficial during the bone remodeling phase of secondary bone healing . Although α‐tocopherol is the major vitamin E isoform utilized by the body, ingestion of tocotrienol‐enriched supplements resulted in superior biomechanical properties of healed bones compared with rats given an α‐tocopherol supplement, suggesting that there may be isoform‐specific effects of vitamin E on bone healing …”
Section: Influence Of Nutritional Supplements On Natural Bone Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin C supplementation accelerated fracture repair that included prominent chondrocyte hypertrophy at day 10 and a well‐developed fibrocartilaginous callus with osteoid formation on day 15, and faster transition of the cartilaginous callus into the bony callus . Unlike vitamin C, vitamin E supplements in the form of α‐tocopherol appear to be most beneficial during the bone remodeling phase of secondary bone healing . Although α‐tocopherol is the major vitamin E isoform utilized by the body, ingestion of tocotrienol‐enriched supplements resulted in superior biomechanical properties of healed bones compared with rats given an α‐tocopherol supplement, suggesting that there may be isoform‐specific effects of vitamin E on bone healing …”
Section: Influence Of Nutritional Supplements On Natural Bone Healingmentioning
confidence: 99%
“…93 Unlike vitamin C, vitamin E supplements in the form of α-tocopherol appear to be most beneficial during the bone remodeling phase of secondary bone healing. 94 Although α-tocopherol is the major vitamin E isoform utilized by the body, ingestion of tocotrienol-enriched supplements resulted in superior biomechanical properties of healed bones compared with rats given an αtocopherol supplement, suggesting that there may be isoform-specific effects of vitamin E on bone healing. 84 Though our understanding of the influence of nutritional supplements on fracture healing has advanced significantly over the years, there are several gaps in our knowledge that should be addressed in future studies.…”
Section: Influence Of Nutritional Supplements On Natural Bone Healingmentioning
confidence: 99%
“…However, the true effect of α-tocopherol on bone is uncertain. A review of studies on Vitamin E in fracture repair suggested that α-tocopherol may impact bone remodeling and healing due to its antioxidant properties but cited the need for more data to be collected (Borhanuddin et al, 2012). In a study using mice genetically unable to import α-tocopherol, mice displayed decreased bone mass due to increased osteoclast fusion.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, el verdadero efecto de E en el hueso es incierto. Una revisión de los estudios sobre el efecto de tocoferoles en la reparación de fracturas sugiere que Vitamina E puede afectar la remodelación ósea y la curación debido a sus propiedades antioxidantes, pero citó la necesidad de más datos para ser recolectados (Borhanuddin et al, 2012). En un estudio utilizando ratones genéticamente incapaces de importar Vitamina E, los ratones mostraron disminución de masa ósea debido al aumento de la fusión de osteoclastos.…”
Section: Discussionunclassified